Utopia for music performance graduates. Is it achievable, and how should it be defined? - Bennett, Dawn (Cambridge University Press, 2007)
For the majority of undergraduate classical music performance students, 'musotopia' isa place where performance ambitions are realised with an international performancecareer. However, given that so few musicians achieve this ambition, should this ideal beredefined? This paper investigates instrumental musicians' careers by exploring therealities of professional practice. Findings reveal the multiplicity of roles in which most musicians engage in order to sustain their careers, and question the concept of amusician as a performer: positing that a musician is rather someone who practiseswithin the profession of music within one or more specialist fields. The diversity ofroles pursued by practising musicians is not considered by the majority of conservatories, thus the enormous potential for the transfer of music graduate skills into the broad cultural industries setting remains largely unrealised. Acceptance of, andpreparation for a more holistic career will enable many more graduates to find their ownmusotopia.